2013
DOI: 10.1371/journal.pone.0060545
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-301a Mediated Regulation of Kv4.2 in Diabetes: Identification of Key Modulators

Abstract: Diabetes is a metabolic disorder that ultimately results in major pathophysiological complications in the cardiovascular system. Diabetics are predisposed to higher incidences of sudden cardiac deaths (SCD). Several studies have associated diabetes as a major underlying risk for heart diseases and its complications. The diabetic heart undergoes remodeling to cope up with the underlying changes, however ultimately fails. In the present study we investigated the changes associated with a key ion channel and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 59 publications
6
49
0
Order By: Relevance
“…Alterations of the spatial heterogeneity of ion channel expression and AP duration have been previously reported in rodent models of diabetes,45, 56, 57 which are consistent, at least in part, with our observation of a preferential prolongation of duration of MAPs in the epicardial/apical region of STZ hearts. The altered regional properties of cardiac tissue may have affected locally the refractoriness of the myocardium, negatively interfering with electrical conduction and pattern of impulse propagation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Alterations of the spatial heterogeneity of ion channel expression and AP duration have been previously reported in rodent models of diabetes,45, 56, 57 which are consistent, at least in part, with our observation of a preferential prolongation of duration of MAPs in the epicardial/apical region of STZ hearts. The altered regional properties of cardiac tissue may have affected locally the refractoriness of the myocardium, negatively interfering with electrical conduction and pattern of impulse propagation.…”
Section: Discussionsupporting
confidence: 93%
“…Reductions of the K + channel subunit, Kv4.2, interacting protein KChIP2, and Ca 2+ channel α‐1C subunit have been proposed as molecular substrates for the decreased Kv currents and I CaL in myocytes from rodent models of diabetes 43, 45, 46, 47, 57, 59. Our electrophysiological data support the possibility that similar alterations occur in the STZ‐hyperglycemic mouse model employed here.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, analysis of miR expression levels in the hearts of various rat and mouse diabetic models also indicated the abnormal expression of miRNA. Further studies demonstrated that miRs contribute to numerous important pathophysiological processes of DCM, including cardiomyocyte hypertrophy, myocardial fibrosis, cardiomyocyte apoptosis, mitochondrial dysfunction, myocardial electrical remodeling and epigenetic modification (27)(28)(29)(30)(31)(32). The present review discusses the possible role of miRs in the pathogenesis of DCM regarding the above-mentioned processes.…”
Section: Introductionmentioning
confidence: 88%
“…miRs are also involved in the pathogenesis of DCM through participating in various pathophysiological processes, such as myocardial electrical remodeling and epigenetic modification (27,31). A significant increase in the level of miR-301 expression and reduction of the voltage gated potassium channel, Kv4.2 expression level were observed in the diabetic (db/db mice) ventricles and miR-301 was validated to modulate Kv4.2 by direct binding on its 3'-UTR (31).…”
Section: Mirs In Cardiomyocyte Apoptosis and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Recently, several studies have highlighted the significance of miRs in maintaining glucose metabolism-associated cell dysfunction (11)(12)(13). For example, miR-130a-3p has been shown to mediate insulin sensitivity (10), and miR-24-3p, miR-146a-5p, miR-194-5p, miR-197-3p, miR-301a-3p and miR-375 are correlated with residual beta cell function in children with new-onset type 1 diabetes mellitus (T1DM) (12).…”
Section: Introductionmentioning
confidence: 99%